Bilateral femoral trochlear hemiarthroplasty for treatment of isolated chondral lesions: A case report. Issue 2 (September 2020) - Gandavaram, Srikanth; Guduri, Venugopal; Singhai, Sharad; Herlekar, Deepak
No abstract available